Penerapan Teknologi Bag Culture pada Budidaya Jahe Merah di Desa Manding Laok Kabupaten Sumenep - Henny Diana Wati; Ika Fatmawati P (Universitas Pahlawan Tuanku Tambusai, 2023)
The purpose of this community service activity is to provide knowledge on cultivating red ginger plants using bag culture technology, namely a system of planting in large plastic sacks. Cultivating red ginger using bag culture technology is carried out due to limited land for cultivating red ginger. The method used in this activity is: participatory counseling, where farmers are directly involved, both in socialization and counseling. Activities carried out in several stages as follows: 1) Coordination with community leaders and partner farmers; 2) Socialization of the implementation of activities; 3) Counseling on appropriate red ginger cultivation techniques, and 4) Training on red ginger cultivation using the bag culture technique. The target achievement of this activity is expected to be able to open the insights and mindset of youth farmer groups in developing the agricultural sector, especially for red ginger commodities. Besides that, this activity can provide knowledge to the public about proper and efficient red ginger cultivation techniques to produce high production as expected.